Pengaruh Metode Karyawisata Terhadap Kreativitas Menggambar Anak di Taman Kanak-Kanak Bani Toifur Kabupaten Nganjuk - Pangastuti, Ratna; Qumillaila, Qumillaila (Al-Athfal: Jurnal Pendidikan Anak, 2017)
Many kinds of learning methods for early age level in stimulate all aspects of its development. One of the methods is karyawisata method. With this method the children directly faced with concrete objects that corresponds to its development stage. In addition to play and and imagine, early children have extraordinary creativity level. In this study researchers want to know how much the influence of karyawisata method against the ability of creativity of early childhood (kindergarten) through activities such as drawing. Where the drawing included in the learning achievement indicator on the Fine motoric aspects. this study use the quantitative approach and analysis technique with product moment in order to measure the scale of "influence" against two variables variable X as bound namely karyawisata method and a variable Y as free namely creativity. While the population is all the students of class B kindergarten of bani Toifur Nganjuk Regency. From the collected data and data processing obtained the result that the table of the value of the "r" product moment with df of 18, on the rank of the significance of 5 percent obtained r_table = 0,444. Because the r_xy on the rank of the significance of 5 percent greater than r_tables, 0.47 > 0,444 dors to write it on the rank of the significance of 5 percent zero hypothesis was rejected, while the alternative hypothesis is received. This means that between both variables X and Y is the influence of the karyawisata method against creativity drawing children in kindergarten of Bani Toifur there is a significant positive correlation.